Factors contributing to online learning satisfaction during Covid-19 pandemic in higher education in Indonesia - Kumalasari, Dewi; Akmal, Sari Zakiah (Jurnal Cakrawala Pendidikan, 2024)
To prevent the transmission of COVID-19, the learning process that used to be face-to-face meetings has turned into online learning. In the online learning context, students’ satisfaction is one of the crucial aspects. However, limited research has looked at the factors contributing to students’ satisfaction in developing countries, including Indonesia. This study investigated the determinants of online learning satisfaction among undergraduate students in Indonesia during the pandemic COVID-19. A total of 267 students aged 17-28 years old (M=20.07, SD=1.40) were participated in this study through accidental sampling technique. This study applied a quantitative approach with six instruments: online learning satisfaction, online learning readiness, academic stress, learner-content interaction, learner-learner interaction, and learner-instructor interaction. Multiple regression analysis showed that only online learning readiness and learner-content interaction were contributed significantly to online learning satisfaction (R2 = .36, F (2,262) = 36.80, p <.001). Furthermore, learner-content interaction had a more considerable contribution (b=1.41, p<.001) to online learning satisfaction than online learning readiness (b=.15, p=.03). The theoretical and practical implications of this study are discussed.